Learning Strategies at Muhammadiyah 2 Krian Elementary School During Covid-19 Pandemic - Muhlasin Amrullah; Rizka Rahmawati (Proceedings of The ICECRS, 2021)
The purpose of this study is to find out the methods and strategies used by SD Muhammadiyah 2 Krian in learning in the midst of the Covid-19 pandemic. This study examines various as-pects, among others: the history of the establishment of SD Muhammamdiyah 2 Krian, learn-ing methods, learning processes, learning strategies and learning breakthroughs during the covid-19 pandemic conducted by teachers who teach at SD Muhammadiyah 2 Krian. In the process of this research using qualitative-descriptive methods. Data retrieval techniques in this study through interviews, observasai and photos during the research process. This study aims to uncover and conclude how the stategi learning during the covid-19 pandemic by SD Mu-hammadiyah 2 Krian, as well as knowing the origin of the establishment of SD Muhammadi-yah 2 krian, as well as schools in general strategies conducted in SD Muhammadiyah 2 krian this by usingblended learning or mixed learning between online and offline, applications used when online is google meet, youtube, or whatsapp and sometimes there are offline or face-to-face in the learning process conducted at SD Muhammadiyah 2 Krian in addition to the break-through in online learning conducted by teachers, there are many challenges in doing the learning process. But even so, learning does not have to be in school and in the classroom of teachers of SD Muhammadiyah 2 Krian still do the learning process through google meet, youtube or some kind of application that exists such as whatsapp in the hope that students can learn despite having to learn from home and ensure the learning process during the covid-19 pandemic is still running, and learning objectives can be achieved even in the current covid-19 pandemic conditions.